Risk factors for bloodstream infections due to extended-spectrum β-lactamase producing Enterobacteriaceae in cancer patients - Ceken, Sabahat; Iskender, Gulsen; Gedik, Habip; Duygu, Fazilet; Mert, Duygu; Kaya, Ali Hakan; Altuntas, Fevzi; Ertek, Mustafa (The Journal of Infection in Developing Countries, 2018)
Introduction: Bloodstream infection (BSI) caused by Enterobacteriaceae is associated with mortality in cancer patients receiving chemotherapy. The aim of this study is to identify the risk factors and outcomes related to BSIs caused by extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in cancer patients. Methodology: Hematology/oncology patients, who were diagnosed with BSIs caused by Enterobacteriaceae by positive blood cultures were evaluated retrospectively. Patients were divided into two groups by ESBL-positive and ESBL-negative Enterobacteriaceae bacteremia. Patients' demographic features, underlying conditions, comorbidity, neutrophil count, duration of neutropenia, antibiotic use in the previous three months before infection, mechanical ventilation, steroid use, central venous catheter implementation, total parenteral nutrition (TPN), hospitalization in the past three months, stay in intensive care unit, quinolone prophylaxis, and history of infection with ESBL-producing Enterobactericeae were evaluated. Risk factors related to BSIs caused by ESBL-producing Enterobacteriaceae and mortality were assessed. Results: A total of 122 patients were evaluated retrospectively. Quinolone propyhlaxis, TPN, infection with Extended Spectrum Beta-Lactamase positive ESBL-P Enterobacteriaceae during the previous three months, treatment with piperasillin-tazobactam or carbapenems in the previous three months were found to be independent risk factors for ESBL-P BSIs. Longer duration of neutropenia before BSI and complication at the beginning of BSI were found to be independent risk factors for mortality related to infection. Conclusions: ESBL-producing Enterobacteriacea should be treated with an appropriate antibiotic that is associated with better outcomes in hematology/oncology patients with BSIs. History of broad-spectrum antibiotic use and stay in hospital in the previous three months should be taken into consideration upon commencing antibiotic therapy.